2021
DOI: 10.3390/brainsci11040415
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 and GATA3 Polymorphisms, Vitamin D3 and Multiple Sclerosis

Abstract: Background: Regulatory T cells (Tregs) alterations have been implicated in the pathogenesis of Multiple Sclerosis (MS). Recently, a crucial role of the X-Linked Forkhead Box P3 (FoxP3) for the development and the stability of Tregs has emerged, and FOXP3 gene polymorphisms have been associated with the susceptibility to autoimmune diseases. The expression of Foxp3 in Tregs is regulated by the transcription factor GATA binding-protein 3 (GATA3) and vitamin D3. The aim of this retrospective case-control study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Vitamin D is notable for its wide-ranging biological functions, which involve, among other things, suppressing metastasis by inhibiting tumor progression, angiogenesis, and cell proliferation, or by apoptosis promotion in cancer cells [5,[16][17][18][19][20]. In lung cancer, specifically, in vivo and in vitro studies have been carried out, showing that 1,25-dihydroxycholecalciferol inhibits growth of lung cancerous cell lines and affects cell cycle regulation in squamous cell carcinoma models [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D is notable for its wide-ranging biological functions, which involve, among other things, suppressing metastasis by inhibiting tumor progression, angiogenesis, and cell proliferation, or by apoptosis promotion in cancer cells [5,[16][17][18][19][20]. In lung cancer, specifically, in vivo and in vitro studies have been carried out, showing that 1,25-dihydroxycholecalciferol inhibits growth of lung cancerous cell lines and affects cell cycle regulation in squamous cell carcinoma models [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…IL1RAPL2 [148], GAD1 [149], EPHA5 [150], HTR1A [151], CADPS (calcium dependent secretion activator) [152], GABRG3 [153], LRFN5 [154] and CXCR1 [155] are expressed in autism spectrum disorders, but these genes might be novel target for AD. GAD2 [156], TAC3 [157], NCR1 [158], IL7R [159], GATA3 [160], FCRL3 [161] and IL18R1 [162] have been reported as most promising biomarkers for early diagnosis and prognosis prediction of multiple sclerosis, but these genes might be novel target for AD. FLT3 [163], CHRNB4 [164], PAK1 [165], CHRNB3 [166], GRIN2A [167], CHRNA6 [168], PENK (proenkephalin) [169], CHRNB4 [170], IGF2 [171], TLR9 [172] and CACNG5 [173] were revealed to serve an important role in Parkinson’s disease, but these genes might be novel target for AD.…”
Section: Discussionmentioning
confidence: 99%
“…The active form of vitamin D, 1,25-Dihydroxyvitamin D3 (1,25(OH)2D3), suppresses autoimmune diseases such as MS by reducing the production of proinflammatory cytokines such as IFN (interferon)-γ, IL (interleukin)-2, and IL-17, as well as enhancing the secretion of anti-inflammatory cytokines such as IL-4 and IL-10 [ 7 11 ]. A recent retrospective case–control study showed that the effect of vitamin D3 on MS susceptibility was not mediated by regulatory T cells (Tregs) [ 12 ]. Increased evidences suggest that decreased vitamin D levels is associated with an abnormal immune response in MS [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%